Catastrophe risk assessment framework of ports and industrial clusters : a case study of the Guangdong province - Cao, Xinhu (2021)
Seaports, as critical infrastructures, are vulnerable to natural catastrophes such as hurricane/typhoon, earthquake, and tsunami. The inoperability of a port caused by these hazards tends to activate domino effects to the adjacent industrial clusters in the hinterland. Limited works addressed high-impact and low-probability (HILP) catastrophe risks and fewer studied industrial cluster risks resulting from catastrophe-induced port disruptions. This paper aims to assess ports and industrial clusters catastrophe risks, based on a three-layer port-cargo-industrial cluster (PCI) model. By using the Guangdong province in China and the typhoon hazard as a case study, we find that the petrochemical industrial cluster is the most vulnerable in the Guangdong province against typhoon-induced port disruptions in the import mode, while the textile and apparel industrial cluster is the least vulnerable. These two industrial clusters exchange rankings under the export mode. Proactive preparations can thus be made to avoid any possible prolonged production downtimes.